Anesthesia and perioperative pain relief in the frail elderly patient - Tom C.R.V Van Zundert; Stephen P Gatt; André A.J van Zundert (Saudi Journal of Anaesthesia, 2023)
Demand for anesthesia and analgesia for the frail elderly is continuously increasing as the likelihood of encountering very elderly, very vulnerable, and very compromised patients has, ever so subtly, increased over the last three decades. The anesthesiologist has, increasingly, been obliged to offer professional services to frail patients. Fortunately, there has been a dramatic improvement in medications, methods of drug delivery, critical monitoring, and anesthesia techniques. Specific methodologies peculiar to the frail are now taught and practiced across all anesthesia subspecialties. However, administering anesthesia for the frail elderly is vastly different to giving an anesthetic to the older patient. Frail patients are increasingly cared for in specialized units—geriatric intensive therapy units, post-acute care services, palliative, hospices, and supportive care and aged care facilities. Several medications (e.g., morphine-sparing analgesics) more suited to the frail have become universally available in most centers worldwide so that best-practice, evidence-based anesthesia combinations of drugs and techniques are now increasingly employed. Every anesthetic and pain management techniques in the frail elderly patient are going to be discussed in this review.